The concept of personality in postmodern stories of the Turkish writer Bouquet Uzuner. - Nigmatullina, Alsu M. (2021)
The relevance of the problem is the need for an artistic understanding of the issues of social reorganization of the country, and to identify the relationship between the inner world of an individual and socio-political events that influenced the artistic specificity of modernist literature. The purpose of this article is to consider the philosophical categories of alienation and loneliness and their embodiment in the literary and artistic field. The main results of the study are in understanding the formation of a new mentality, in the formation of a new personality, designed to be perceived as not only a literary phenomenon, but also as socio-political and cultural-historical one.